Meaning Making Process Through Images And Soundscape - F. Sumaylo, Dennis John (2015)
With the continuous expansion of urban areas in the country, it is undeniable that what was used to be the original heart of the city is neglected as development in almost all sectors including education, health, and commerce are sprawling away from the city center. As time passes, physical changes happen. With these changes, the narratives of the people who frequent the place also change. Various efforts have been made to document the street using photographs. With great details and vivid colors, photographers have produced outputs that are published and exhibited. But with technology and the continuous desire of people to visualize almost anything, the level of appreciation and depreciation changes specially with the advent of 3D, 4D, and virtual reality